Colletotrichum Crown Rot (Anthracnose Crown Rot) of Strawberries - Natalia A. Peres; Steven J. MacKenzie (EDIS)
Colletotrichum crown rot is caused by the fungi Colletotrichum gloeosporioides and Colletotrichum fragariae. Both pathogens kill strawberry plants by aggressively invading crown tissue. Crown rot is a serious disease in warm production regions, such as those in the southeastern United States. This revised 3-page fact sheet was written by Natalia A. Peres and Steven J. MacKenzie, and published by the UF Department of Plant Pathology, September 2012.